Pengembangan Digital Book Sebagai Sumber Belajar Aritmatika Sosial Dengan Pendekatan Kontekstual - Eni Nurhayati; M. Zainudin; Ima Isnaini Taufiqur Rohmah (LPPM Politeknik Pratama, 2023)
This development research aims to produce a digital book product as a social arithmetic teaching material with a contextual approach and to determine the feasibility of a digital book developed through expert validation and student’s readability tests. This development research method uses the 4D development model from Thiagarajan which has four stages, namely define, design, develop, and disseminate. This development research produces flipbook-based digital book products so that they are more interactive for learning and are also accompanied by back sound so that learning is more varied. The results of the feasibility assessment of digital book products that have been validated by material expert get very good scores with a percentage of 93%, in the validation of media expert get a good scores with a percentage of 80% and in the mathematics teacher’s assessment get a very good score with a percentage of 95%. Then on the digital book readability test by students got a very good score with a percentage of 87%. Based on the results of the assessment obtained it can be concluded that the digital book can be used as an alternative teaching material in learning social arithmetic.